Recombinant Culicoides obsoletus complex allergens stimulate antigen‐specific T cells of insect bite hypersensitive Shetland ponies in vitro. Issue 6 (8th September 2015) - Meulenbroeks, Chantal; van der Meide, Nathalie M.A.; Willemse, Ton; Rutten, Victor P.M.G.; Tijhaar, Edwin
Abstract : Background: Ponies may suffer from Insect bite hypersensitivity (IBH), an allergic IgE‐mediated pruritic skin disorder, induced by allergens from biting midges of the Culicoides spp. Hypothesis/Objectives: To determine whether recombinant Culicoides obsoletus allergens are able to activate T cells of ponies exposed to C. obsoletus and whether these allergen‐specific responses differ between IBH‐affected and healthy ponies. Animals: Ten IBH‐affected Shetland ponies and 10 age‐matched healthy controls taken from the same stables, to ensure similar exposure to midges. Method: Peripheral blood mononuclear cells (PBMC) were cultured with two different pools of recombinant C. obsoletus complex allergens to expand the allergen‐specific T cells. These PBMC cultures were subsequently co‐cultured with mature dendritic cells (DCs) loaded with the same antigens. Induction of Th1, Th2 and regulatory T (Treg) cells in these DC/PBMC co‐cultures was assessed by analysis of IFN‐γ, IL‐4, IL‐10 and FoxP3 expression levels using quantitative RT‐PCR and phenotyping by flow cytometry. Results: Recombinant C. obsoletus allergens increased IFN‐γ mRNA expression levels, percentages of IFN‐γ expressing (Th1) cells and CD25 high FoxP3 + IL‐10 + Tregs compared to unstimulated DC/PBMC co‐cultures. Stimulation of IL‐4 expressing Th2 cells by the recombinant allergens was far less pronounced. The DC/PBMC co‐cultures did not reveal significant differences between healthy and IBH‐affected ponies for any of the analysed parameters, except for higher IL‐4 mRNA levels in IBH affected ponies after stimulation with one of the two allergen pools. Conclusion and clinical importance: The recombinant C. obsoletus complex allergens can stimulate antigen‐specific Th1 and IL10 producing Treg cells and are therefore promising candidates for the immunotherapy of IBH. Abstract : Background Ponies may suffer from Insect bite hypersensitivity (IBH), an allergic IgE‐mediated pruritic skin disorder, induced by allergens from biting midges of the Culicoides spp.Hypothesis/Objectives To determine whether recombinant Culicoides obsoletus allergens are able to activate T‐cells of ponies exposed to C. obsoletus and whether these allergen‐specific responses differ between IBH‐affected and healthy ponies.Conclusion and clinical importance The recombinant C. obsoletus complex allergens can stimulate antigen‐specific Th1 and IL10 producing Treg cells and are therefore promising candidates for immunotherapy of IBH.